TathbÃ®q TiknÃ»lÃ»jiyÃ¢ (IstirÃ¢tÃ®jiyah al-KharÃ®thah al-Dzihniyah) li Hilli Musykilah Ta’lÃ®m MufradÃ¢t al-Lughah al-’Arabiyah Lada ThullÃ¢b al-Fashl al-SÃ¢bi’ fÃ® al-Madrasah al-TsÃ¢nawiyah "Nurul Jadid Banyuputih - Situbondo" - Fuâ€™adah, Shofwatul (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2020)
The inhibiting factor for students having difficulty in learning Arabic is that vocabulary mastery is still very limited, even though the vocabulary is an elementary language that must be mastered by foreign language learners including the Arabic Language. Therefore learning methods and strategies are very influential in the learning process and student’s motivation to study. Learning strategies included in the design of domain learning technology. So the teacher in this school uses mind mapping strategies to solve the student’s problem in mastering Arabic vocabulary. In this study, the researcher used a qualitative method. While the process, the researcher has a source of data from the mufradat/vocabulary learning process as well as the students involved in it. This paper discusses the implementation of learning technology (mind mapping strategy) to solve the problem of learning mufradat. And The results of this study prove that the mind mapping strategy help to improve mufradat mastery of the students and them following the learning process with pleasure.